Structure-driven biomimetic self-morphing composites fabricated by multi-process 3-D printing. (August 2019) - zhao, Che; Ren, Luquan; Song, Zhengyi; Deng, Linhong; Liu, Qingping
Abstract: The self-morphing mechanism of some plant organs had inspired researchers to facilitate the realization of smart composites, and 3-D printing had shown its superiority in this area. However, composites fabricated directly by the 3-D printer are too soft, and complexity of the ink preparation is still very high. In this study, we presented a new method which combined 3-D printing technique and impregnation process to develop the biomimetic fibre-reinforced composites with programmable self-morphing properties. The new composites are reinforced by the continuous fibers which can effectively increase their mechanical property like cellulose fibrils in plant tissue. Moreover, matrices of the composites are made by the commercial water swelling rubbers, thus extend the choice of the compatible materials and reduce their preparation cost. Finally, the flexible method helps the smart composites to undergo specific shape transformations, like bending, twisting, and other inhomogeneous deformation.